Pengembangan Produk Unggulan Badan Usaha Milik Desa Berbasis E-Marketing - Chairatun Nisa'il Firdausi Madjid; Jannatul Firdaus; Agung Winarno; Agus Hermawan (Universitas Muhammadiyah Yogyakarta, 2022)
Social media and e-commerce, such as Instagram and Shopee, are market platforms in great demand by the public because of the ease of transactions and their product variety. The existence of these media can help Bumdes Sambigede, Sumberpucung District, Malang Regency in reaching out to potential consumers widely. The purpose of this service is to improve the knowledge and skills of managers in marketing BUMDES products based on e-marketing. The research was held through surveys, and direct experiments/practices carried out through training and mentoring. The results of this activity were in the form of a BUMDES product brand logo, rengginang product stickers/labels, BUMDES Instagram media, and a marketplace at Shopee to promote products widely by maximizing existing features and supporting applications.